Spandex, el destape cultural de la Transición: Homosexualidad y performance en tiempos de SIDA. - PETRIC TOBAR, ANDRÉS (Nomadías)
The following article problematizes the influence of public knowledge about AIDS on Spandex's performances: underground parties celebrated in Santiago de Chile between 1991 and 1992, which were pioneer manifestations of entertainment that brought together many identities, especially LGBTI people, boosting a metropolitan cultural uncovering longed for who suffered sociopolitical violence during military dictatorship (1973-1990). For this, we interview to five gay men which produced or just were to the parties for to know about motivations, dynamics and effects of performances and its relationship with public knowledge about AIDS.